Investment intentions and financial decisions of women investors: A bibliometric analysis for future research - Pratichi Dash; Susanta Kumar Mishra (Global Business & Finance Review (GBFR), 2024)
Purpose: Making investment decisions has become more difficult for women investors in recent decades due to the prevalence of irrational behaviour. This research aims to use bibliometric analysis to fill a gap in the current literature on women's investing aspirations. This analysis will offer a thorough overview and suggest potential areas for further research. Design/methodology/approach: This study conducted a search on the Web of Science databases to identify 29 publications published between 2013 and 2023. Afterwards, this study used the PRISMA method to evaluate these articles for systematic reviews and meta-analyses. The VOS viewer software was utilized for conducting biblio-metric analysis. Findings: The outcomes of this study shows that women's financial literacy, risk behavior, and financial planning are all correlated with the decisions they make with their own money. Various elements, including demographics, society, and psychology, influence female investor's intention to invest. Research limitations/implications: To ensure the accuracy and reliability of the findings, data for bibliometric analysis was extracted exclusively from a single database, namely Web of Science. Subsequent investigations have the potential to expand the systematic literature review by incorporating various databases containing diverse soft-ware applications, as well as distinct theories and methodologies for future research. Originality/value: This study assesses the existing literature and enhance the conceptual and social framework sur-rounding the investment intention and financial decision-making of women investors. The findings offer valuable insights for firms, financial institutions, and policy makers to a thorough comprehension on the intentions of women investors. This may help enhancing the financial sector and economy, both in theory and in practice.
Keywords: 650; Investment intention; Financial decision; PRISMA; Bibliometric study; Content analysis; Women investor